Psychological factors of college students’ learning pressure under the online education mode during the epidemic - Fu, Leiming; Li, Junlong; Chen, Yifei (Frontiers in Psychology, 2022)
Internet technology is slowly penetrating into all aspects of people's lives and has had a huge impact and change on people's lives. With the repeated outbreak of the epidemic in recent years, online education has been increasingly applied to the study and life of college students. The epidemic has lasted for three years, while the life of college students is only four years. In recent years, most of the campus study and life of college students have been carried out in the online education mode. This not only changed the mode of class, but also changed the mental health of college students. Taking the online education model during the epidemic as the research background, this paper selects the psychological factors of college students' learning pressure to analyze, combined with the design and implementation of the questionnaire, to understand the impact of online education on college students' cognition, emotion, willpower and social interaction. The purpose is to find out the psychological factors of college students' learning pressure under the online education mode, and to propose effective solutions. The analysis of the psychological factors of college students' learning pressure in the form of questionnaires is more accurate than other forms of experimental investigation, the efficiency is increased by 32%, and the accuracy is also increased by 18%.